Myanmar migration in a time of transformation: 2011-2020 [in Burmese] - Van Campenhout, Bjorn; Minot, Nicholas; Kabir, Razin; Vos, Rob; Narayanan, Sudha; Rice, Brendan; Aredo, Samson Dejene (International Food Policy Research Institute, 2021)
Rural out-migration to both domestic and international destinations counts among the key phenomena that defined a decade of transformation in Myanmar from the 2011 economic reforms until the onset of the COVID-19 pandemic in 2020. We analyze data from four surveys conducted in different areas of rural Myanmar from 2015 to 2018, along with relevant literature, to highlight trends in migration and its contributions to economic growth and rural development. Studied areas include Mon State, as well as parts of the Ayeyarwady Delta, the Central Dry Zone, and Shan State.